Growth and optical caracteristics of the CsI:Li scintillator crystal for use as radiation detector (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Materials capable of converting ionizing radiation into light photons are called scintillators, some have specific efficiencies for certain applications and types of radiation, e.g. gamma, X-ray, alpha, beta and neutrons. CsI:Tl and NaI:Tl crystals are commonly found in the market because they have several applications, but few studies have been done on lithium doped cesium iodide crystal (CsI:Li). The lithium element, in this crystal used as a dopant, is also exploited as a converter for neutron detection, as it has a shock section of 940 barns for thermal neutrons. The study of the CsI:Li crystal is convenient considering the natural abundance of the lithium element with 7.5%, besides the interest in having a low cost national scintillator material with an opportunity to search the response of a detector for different types of radiation. The CsI:Li crystal was grown with molar concentration 10-4 to 10-1, using the vertical Bridgman technique. The parameters involved in the growth process were investigated. The transmittance was evaluated in the spectral region from 190 nm to 1100 nm.  Luminescence emission spectra for the CsI:Li crystal were evaluated by photometric analysis of the crystal  stimulated with a 137Cs (662 keV) source in front of the coupled sample at the monochromator input. The crystals showed of maximum luminescence intensity at the wavelength of 420 nm. The response of the  scintillators when excited with gamma radiation of 241Am, 133Ba, 22Na, 137Cs, 60Co and neutron radiation from the AmBe source, with energy range of 1 MeV to 12 Mev was evaluated.